Association of school absence and exclusion with recorded neurodevelopmental disorders, mental disorders, or self-harm: a nationwide, retrospective, electronic cohort study of children and young people in Wales, UK. (January 2022) - John, Ann; Friedmann, Yasmin; DelPozo-Banos, Marcos; Frizzati, Aura; Ford, Tamsin; Thapar, Anita
Summary: Background: Poor attendance at school, whether due to absenteeism or exclusion, leads to multiple social, educational, and lifelong socioeconomic disadvantages. We aimed to measure the association between a broad range of diagnosed neurodevelopmental and mental disorders and recorded self-harm by the age of 24 years and school attendance and exclusion. Methods: In this nationwide, retrospective, electronic cohort study, we drew a cohort from the Welsh Demographic Service Dataset, which included individuals aged 7–16 years (16 years being the school leaving age in the UK) enrolled in state-funded schools in Wales in the academic years 2012/13–2015/16 (between Sept 1, 2012, and Aug 31, 2016). Using the Adolescent Mental Health Data Platform, we linked attendance and exclusion data to national demographic and primary and secondary health-care datasets. We identified all pupils with a recorded diagnosis of neurodevelopmental disorders (ADHD and autism spectrum disorder [ASD]), learning difficulties, conduct disorder, depression, anxiety, eating disorders, alcohol or drugs misuse, bipolar disorder, schizophrenia, other psychotic disorders, or recorded self-harm (our explanatory variables) before the age of 24 years. Outcomes were school absence and exclusion. Generalised estimating equations with exchangeable correlation structures using binomial distribution with the logit link function were used to calculate odds ratios (OR) for absenteeism and exclusion, adjusting for sex, age, and deprivation. Findings: School attendance, school exclusion, and health-care data were available for 414 637 pupils (201 789 [48·7%] girls and 212 848 [51·3%] boys; mean age 10·5 years [SD 3·8] on Sept 1, 2012; ethnicity data were not available). Individuals with a record of a neurodevelopmental disorder, mental disorder, or self-harm were more likely to be absent or excluded in any school year than were those without a record. Unadjusted ORs for absences ranged from 2·1 (95% CI 2·0–2·2) for those with neurodevelopmental disorders to 6·6 (4·9–8·3) for those with bipolar disorder. Adjusted ORs (aORs) for absences ranged from 2·0 (1·9–2·1) for those with neurodevelopmental disorders to 5·5 (4·2–7·2) for those with bipolar disorder. Unadjusted ORs for exclusion ranged from 1·7 (1·3–2·2) for those with eating disorders to 22·7 (20·8–24·7) for those with a record of drugs misuse. aORs for exclusion ranged from 1·8 (1·5–2·0) for those with learning difficulties to 11·0 (10·0–12·1) for those with a record of drugs misuse. Interpretation: Children and young people up to the age of 24 years with a record of a neurodevelopmental or mental disorder or self-harm before the age of 24 years were more likely to miss school than those without a record. Exclusion or persistent absence are potential indicators of current or future poor mental health that are routinely collected and could be used to target assessment and early intervention. Integrated school-based and health-care strategies to support young peoples' engagement with school life are required. Funding: The Medical Research Council, MQ Mental Health Research, and the Economic and Social Research Council. Translation: For the Welsh translation of the abstract see Supplementary Materials section.